Antitumor Effects and Mechanisms of Metabolic Syndrome Medications on Hepatocellular Carcinoma - Oura K; Morishita A; Tani J; Masaki T (Journal of Hepatocellular Carcinoma, 2022)
Kyoko Oura, Asahiro Morishita, Joji Tani, Tsutomu Masaki Department of Gastroenterology and Neurology, Faculty of Medicine, Kagawa University, Kagawa, JapanCorrespondence: Kyoko Oura, Department of Gastroenterology and Neurology, Kagawa University, 1750-1 Ikenobe, Miki, Kida, Kagawa, Japan, Tel +81-87-891-2156, Fax +81-87-891-2158, Email oura.kyoko@kagawa-u.ac.jpAbstract: Liver cancer has a high incidence and mortality rate worldwide, with hepatocellular carcinoma (HCC) being the most common histological type. With the decrease in the number of newly infected patients and the spread of antiviral therapy, hepatitis virus-negative chronic liver diseases including steatohepatitis are increasingly accounting for a large proportion of HCC, and an important clinical characteristic is the high prevalence of metabolic syndrome including hypertension, type 2 diabetes (T2D), dyslipidemia, and obesity. Since patients with steatohepatitis are less likely to undergo surveillance for early detection of HCC, they may be diagnosed at an advanced stage and have worse prognosis. Therefore, treatment strategies for patients with HCC caused by steatohepatitis, especially in advanced stages, become increasingly important. Further, hypertension, T2D, and dyslipidemia may occur as side effects during systemic treatment, and there will be increasing opportunities to prescribe metabolic syndrome medications, not only for originally comorbid diseases, but also for adverse events during HCC treatment. Interestingly, epidemiological studies have shown that patients taking some metabolic syndrome medications are less likely to develop various types of cancers, including HCC. Basic studies have also shown that these drugs have direct antitumor effects on HCC. In particular, angiotensin II receptor blockers (a drug group for treating hypertension), biguanides (a drug group for treating T2D), and statins (a drug group for treating dyslipidemia) have shown to elucidate antitumor effects against HCC. In this review, we focus on the antitumor effects of metabolic syndrome medications on HCC and their mechanisms based on recent literature. New therapeutic agents are also increasingly being reported. Analysis of the antitumor effects of metabolic syndrome medications on HCC and their mechanisms will be doubly beneficial for HCC patients with metabolic syndrome, and the use of these medications may be a potential strategy against HCC.Keywords: hypertension, angiotensin II receptor blockers, diabetes, biguanide, dyslipidemia, statin